Maternal perspectives on the return of genetic results: Context matters12. Issue 1 (13th December 2012) - Lakes, Kimberley D.; Vaughan, Elaine; Lemke, Amy; Jones, Marissa; Wigal, Timothy; Baker, Dean; Swanson, James M.; Burke, Wylie
Abstract The objectives of this study were to study maternal preferences for the return of their child's genetic results and to describe the experiences, perceptions, attitudes, and values that are brought to bear when individuals from different racial and cultural backgrounds consider participating in genetic research. We recruited women with diverse sociodemographic profiles to participate in seven focus groups. Twenty‐eight percent of participants self‐identified as Hispanic; 49% as White, non‐Hispanic; and 21% as Asian or Asian American. Focus groups were conducted in English or Spanish and were audio‐recorded and transcribed verbatim. Transcripts were analyzed using qualitative thematic methods. Results indicated that preferences and decisions regarding the return of results may depend on both research and individual contextual factors. Participants understood the return of results as a complex issue, where individual and cultural differences in preferences are certain to arise. Another key finding was that participants desired an interpersonal, dynamic, flexible process that accommodated individual preferences and contextual differences for returning results. Our findings indicate a need to have well‐developed systems for allowing participants to make and change over time their choices regarding the return of their child's genetic results. © 2012 Wiley Periodicals, Inc.